2004
DOI: 10.1097/01.tp.0000115346.85679.34
|View full text |Cite
|
Sign up to set email alerts
|

Functional heterogeneity of mitochondria after cardiac cold ischemia and reperfusion revealed by confocal imaging

Abstract: Background. Mitochondria play a critical role in ischemia-reperfusion injury of the heart. The purpose of the present study was to analyze the intracellular region-specific functional state of mitochondria after cold ischemia-reperfusion in a rat heart transplant model.Methods. Imaging of the mitochondrial functional state in situ in nonfixed myocardial fibers was performed by confocal microscopy of mitochondrial flavoprotein autofluorescence as redox state indicator; fluorescence of Rhod-2, a specific probe f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…In theory, a heterogeneous population may represent the existence of subpopulations of mitochondria that have relatively reduced capacity to generate secretagogues and thus constitute a therapeutic target for increased insulin secretion. To date, the phenomenon of mitochondrial heterogeneity has been studied in several cell types (7)(8)(9)(10)(11)(12) but not in ␤-cells.…”
Section: Results-wementioning
confidence: 99%
See 1 more Smart Citation
“…In theory, a heterogeneous population may represent the existence of subpopulations of mitochondria that have relatively reduced capacity to generate secretagogues and thus constitute a therapeutic target for increased insulin secretion. To date, the phenomenon of mitochondrial heterogeneity has been studied in several cell types (7)(8)(9)(10)(11)(12) but not in ␤-cells.…”
Section: Results-wementioning
confidence: 99%
“…Importantly, TMRE equilibration is rapid due to high permeability across membranes and it does not inhibit mitochondrial respiration in low concentrations (29). The dye concentrations used are lower than those previously reported in intact cell studies (7,8,29,30,31). This enabled minimal levels of cytotoxicity and self-quenching of the dyes.…”
Section: Mitochondria In Pancreatic Islets Are Metabolically Heterogementioning
confidence: 95%
“…For example, studies investigating the ischemia-reperfusion model has shown that rat cardiomyocytes exhibit higher levels of heterogeneity after reperfusion. 30,31 Moreover, increased nutrient levels have been shown to increase mitochondrial membrane potential heterogeneity in pancreatic ␤ cells. 13 We report that an increase in mitochondrial heterogeneity coincides with the progression of RRECs through apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneous distribution of mitochondria throughout the cardiomyocyte, gives rise to functionally diverse subpopulations that are also subjected to physical and therefore functional alteration by fusion and fission cycles during physiological conditions and with acute and chronic CV disease [213]. Able to regulate mitochondrial morphology, fusion and fission events affect not only the mitochondrial membranes, but also the mitochondrial matrix, with respective sharing and splitting of matrix compartments.…”
Section: Mitochondrial Morphology and Structurementioning
confidence: 99%
“…I/R injury has been shown to result in increased mitochondrial heterogeneity across numerous functional parameters, including Ca 21 content, redox status and membrane potential, as measured by fluorescent confocal microscopy [207,213]. The rate of OxPhos was shown to decrease only in subsarcolemmal mitochondria, following 45 minutes global ischemia [214], while the loss of Dc M with I/R was shown to propagate [215] longitudinally from point of initiation, with overall heterogeneity in the spatial distribution of mitochondria affected [206].…”
Section: Mitochondrial Morphology and Structurementioning
confidence: 99%